The Navajo Yearbook - Young, Robert W., Comp.; Navajo Tribe Public Relations and Information Dept., Window Rock, AZ.; Bureau of Indian Affairs (Department of Interior), Washington, DC. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1961)
The Navajo Yearbook began as an annual report to relate progress in carrying out provisions of the Navajo-Hopi Long Range Rehabilitation Act (P.L. 474 - 81st Congress), but the scope has been expanded to include all programs conducted on the reservation. This volume, the eighth in the series, is designed to reflect changing problems, changing programs, and overall progress toward realization of the objectives of the Act, and provides specific information with reference to the period 1959-61. Categories include those programs aimed primarily at solving economic and social problems of education, health, and welfare, and facilitating programs such as road construction. The purpose of the yearbook is to meet the need for information in consolidated form for program coordination. (JH)
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: American Indians; Economic Development; Education; Educational Environment; Educationally Disadvantaged; English (Second Language); Federal Legislation; Health; Industrialization; Land Use; Law Enforcement; Navajo; Religion; Relocation; Residential Schools; Welfare; Navajo (Nation); Hopi (Tribe)